Protection Of Civilians In Armed Conflict In Libya - Anesty Amelia Kartika, Joko Setiyono , Soekotjo Hardi Winoto (Diponegoro Law Journal, 2013)
The demonstrations that occurred in several cities demanding the resignation of Gaddafi's Libya was initially done by performing acts of vandalism. The actions taken by demonstrators bigger and more frequent conflict with the security forces. With the extent of the actions of the Gaddafi government, make the demonstrators feel that the only way to end the Gaddafi regime is to take the armed resistance. The moment the rebels weakened condition, the Security Council to seek negotiations with the Libyan government. However, the effort was rejected by the government of Gaddafi. Then the Security Council to send peacekeepers. Peacekeeping function is to protect the civilian population. The Security Council issued a resolution to the enforced of no-fly zone. Initially the conflict in Libya is a civil war. However, with the inclusion of the intervention of the NATO (North Atlantic Treaty Organization) based on a mandate from the Security Council to make this conflict to an international impact. Responsibility of the government to protect the Libyan civilian population is to prosecute the son of Gaddafi Saif al-Islam. Libyan state in transition, making the debate where Saif will be tried. ICC (International Criminal Court) felt that Libya has not been able to prosecute Saif. The aim is to ensure a fair trial for Saif crack when arrested.